A Novel Sodium Alginate-Carnauba Wax Film Containing Calcium Ascorbate: Structural Properties and Preservative Effect on Fresh-Cut Apples - Ximeng Lin; Hanyu Zhang; Xi Guo; Yimin Qin; Peili Shen; Qiang Peng (Molecules, 2023)
In order to improve the mechanical properties, nutritional value and fresh-keeping ability of conventional sodium alginate edible composite membranes, a new type of edible composite film was prepared by adding water-blocking agent carnauba wax, plasticizer glycerin, antioxidant and nutritional enhancer sodium ascorbate on a basis of traditional sodium alginate composite film. In this study, the physical, mechanical and structural properties of different film components were investigated. The results showed the components did not simply combine, but produced interaction forces which improved the stability and mechanical properties of composite film. When the amount of calcium ascorbate was 0.4%, the water vapor transmittance of the composite film reached a minimum of 0.65 g·mm/(cm2·d·kPa), and the tensile strength and elongation at break reached the maximum, which were 398.64 MPa and 17.93%, respectively. Additionally, the sodium alginate-carnauba wax film exhibited better performance on the preservation of fresh-cut apples. Compared with other composite films, the color and hardness of fresh-cut apples coated with this composite film were better maintained, and the losses of titration acid content and soluble solid content were reduced. Moreover, the weight loss rate, increase in polyphenol oxidase activity and total colony count were inhibited. All results determined that the edible film has good application value in the field of fresh-cut fruit preservation, which provides a theoretical basis for further research on edible film.